BIOGRAPHICAL RESEARCH IN THE SERVICE OF ANTHROPOLOGY: WIKTOR BURDA, MARCIN CZERMIŃSKI AND JÓZEF OBRĘBSKI – FROM DOCUMENTING LOCALITY TO CREATING GLOBAL NARRATIVES (Slavic Studies, 2025)
The article analyzes the biographies of three figures – Wiktor Burda, Marcin Czermiński, and Józef Obrębski – from the perspective of cultural and regional anthropology. It demonstrates how their individual lives and scholarly or economic activities influenced the formation of local and global cultural narratives and identities. Using an interdisciplinary approach, the study explores the interplay between biography, locality, and globality, proposing biographical research as a tool not only for documentation but also for the interpretation of cultural transformation. Particular emphasis is placed on regional identity as a dynamic and negotiated process, as well as the contribution of Polish intellectuals and entrepreneurs to the development of the Balkans in the context of political and social changes at the turn of the 20th century.
Keywords: biographical research; anthropology; W. Burda; M. Czermiński; J. Obrębski